1993
DOI: 10.4269/ajtmh.1993.49.520
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Single Specimens of the Anopheles Gambiae Complex by the Polymerase Chain Reaction

Abstract: A ribosomal DNAâ€"polymerase chain reaction (PCR) method has been de veloped for species identification of individuals of the five most widespread members of the Anopheles gambiae complex, a group ofmorphologically indistinguishable sibling mos quito species that includes the major vectors of malaria in Africa. The method, which is based on species-specific nucleotide sequences in the ribosomal DNA intergenic spacers, may be used to identify both species and interspecies hybrids, regardless of life stage, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1,237
1
7

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,420 publications
(1,249 citation statements)
references
References 0 publications
4
1,237
1
7
Order By: Relevance
“…could be An. merus as the protocol by Scott et al (1993) used in this study did not include primers to identify An. merus which Masendu et al (2005) reported as being common in some parts of Zimbabwe.…”
Section: Resultsmentioning
confidence: 99%
“…could be An. merus as the protocol by Scott et al (1993) used in this study did not include primers to identify An. merus which Masendu et al (2005) reported as being common in some parts of Zimbabwe.…”
Section: Resultsmentioning
confidence: 99%
“…Adults were assigned to members of the An. gambiae cryptic‐species complex on the basis of morphological tests and molecular analyses (Gillies & Coetzee, 1987; Santolamazza et al., 2008; Scott, Brogdon, & Collins, 1993). …”
Section: Methodsmentioning
confidence: 99%
“…were processed for species determination using PCR 32 and P falciparum infection using an enzyme-linked immunosorbent assay 33 . Wild caught A gambiae s.l.…”
Section: Entomological Collectionsmentioning
confidence: 99%